WISP-1 Promotes Epithelial-Mesenchymal Transition in Oral Squamous Cell Carcinoma Cells via the miR-153-3p/Snail Axis - Chang, An-Chen; Lien, Ming-Yu; Tsai, Ming-Hsui; Hua, Chun-Hung; Tang, Chih-Hsin (Cancers, 2019)
Around half of all patients with oral squamous cell carcinoma (OSCC) present with lymphatic metastasis, a strong predictor of poor survival. Improving survival rates depends on preventing the first step in the “invasion-metastasis cascade,” epithelial-to-mesenchymal transition (EMT), and developing antilymphangiogenesis therapies that antagonize lymphatic metastasis. The extracellular matrix-related protein WISP-1 (WNT1-inducible signaling pathway protein-1) stimulates bone remodeling and tumor progression. We have previously reported that WISP-1 promotes OSCC cell migration and lymphangiogenesis induced by vascular endothelial growth factor C (VEGF-C). This investigation sought to determine the role of WISP-1 in regulating EMT in OSCC. Our analysis of oral cancer data from The Cancer Genome Atlas (TCGA) database revealed significant and positive associations between levels of WISP-1 expression and clinical disease stage, as well as regional lymph node metastasis. We also found higher levels of WISP-1 expression in serum samples obtained from patients with OSCC compared with samples from healthy controls. In a series of in vitro investigations, WISP-1 activated EMT signaling via the FAK/ILK/Akt and Snail signaling transduction pathways and downregulated miR-153-3p expression in OSCC cells. Our findings detail how WISP-1 promotes EMT via the miR-153-3p/Snail axis in OSCC cells.